Behavior for Time Invariant Finite Dimensional Discrete Linear Systems - Sylviani, Sisilia; Garminia, Hanni; Astuti, Pudji (Journal of Mathematical and Fundamental Sciences, 2013)
The behavior of a dynamical system, in Willems's point of view, is the set of all trajectories of the system. Fuhrmann defines a behavior as a linear, shift invariant, and complete subspace of z-1Fm[[z-1]], the vector space consisting of power series in z-1 with coefficients in signal space W=Fm. In this paper we show that the behavior of a finite dimensional, time invariant discrete linear system in Willems's setting is also a behavior according to Fuhrmann's.